Structural study of joints in Albody region-Lattakia (Latakia University Journal -Basic Sciences Series, 2020)
Study of joints in Body region at Lattakia showed that the first dominant principal direction of joints is NW-SE (°120-°150) and it is tensional joints distributed in the middle of studied region at formation from Senonian in age. this dominant principal direction is late Cretaceous in age. The second principal direction NE-SW (°30-°50)  of joints distribute in  eastern and northeastern studied region at Cenomanian to Maastrichtian and Paleogene formations . it's clear the relation of  NE-SW joints distribution area with  distribution area of normal faults from the same direction, this show the tensional origin relation of NE-SW joints with  NE-SW normal faults. We suggest a Miocene-Pliocene to this direction.E-W direction of joint distribute in western studied area and it is Paleogene in age. The number of joint in 10 meter and the aperture width of joint shows highest values around Albody village and at southeastern study region where meets all the joints direction and there were two NE-SW normal fault, we suppose that it plays a role in increase this values.